Can recyclable packaging enhance consumers’ willingness to buy? The mediating role of corporate social responsibility perception - SHI, Haifeng (Institutional Knowledge at Singapore Management University, 2024)
The usage of recyclable packaging is a manifestation of corporate social responsibility and conforms to the trend of green and sustainable development. In recent years, with the rapid growth of the environmental awareness, consumers tend to choose more environmentally friendly and recyclable packaged products. Therefore, in order to better promote the usage of recyclable packaging, it is necessary to conduct in-depth research on why consumers choose recyclable packaging. Aiming to explore the impact of recyclable packaging on consumer behavior and its underlying mechanism, this study receives 314 questionnaire surveys all over the country, and adopts ANOVA and process model analyses to verify the main effects and the mediating role of consumers’ perception of CSR between the recyclable packaging and consumer behavior (consumer purchase intention, consumer satisfaction and consumers’ willingness to pay premium). Meanwhile, consumers’ environmental attitudes play a significant moderating role between recyclable packaging and consumers’ perception of CSR. Compared with the direct impact of recyclable packaging on consumer behavior, the moderated mediation effect of consumers’ perception of CSR is more significant, that is, when increasing consumers’ perception of CSR, those who have higher environmental attitudes tend to have stronger consumer purchase intention on recyclable packaging; and when purchasing products with recyclable packaging, they tend to generate more consumer satisfaction and more willingness to pay premium.